Efficient identity-based authenticated key agreement protocol with provable security for vehicular ad hoc networks. (April 2018) - Dang, Lanjun; Xu, Jie; Cao, Xuefei; Li, Hui; Chen, Jie; Zhang, Yueyu; Fu, Xiaotong
In vehicular ad hoc networks, establishing a secure channel between any two vehicles is fundamental. Authenticated key agreement is a useful mechanism, which can be used to negotiate a shared key for secure data transmission between authentic vehicles in vehicular ad hoc networks. Among the existing identity-based two-party authenticated key agreement protocols without pairings, there are only a few protocols that provide provable security in strong security models such as the extended Canetti–Krawczyk model. This article presents an efficient pairing-free identity-based one-round two-party authenticated key agreement protocol with provable security, which is more suitable for real-time application environments with highly dynamic topology such as vehicular ad hoc networks than the existing identity-based two-party authenticated key agreement protocols. The proposed protocol is proven secure under the passive and active adversaries in the extended Canetti–Krawczyk model based on the Gap Diffie–Hellman assumption. The proposed protocol can capture all essential security attributes including known-session key security, perfect forward secrecy, basic impersonation resistance, key compromise impersonation resistance, unknown key share resistance, no key control, and ephemeral secrets reveal resistance. Compared with the existing identity-based two-party authenticated key agreement protocols, the proposed protocol is superior in terms of computational cost and running time while providing higher security.